Binding Mode Multiplicity and Multiscale Chirality in the Supramolecular Assembly of DNA and a π‐Conjugated Polymer. Issue 23 (18th November 2020) - Fossépré, Mathieu; Tuvi‐Arad, Inbal; Beljonne, David; Richeter, Sébastien; Clément, Sébastien; Surin, Mathieu
Abstract: Water‐soluble π‐conjugated polymers are increasingly considered for DNA biosensing. However, the conformational rearrangement, supramolecular organization and dynamics upon interaction with DNA have been overlooked, which prevents the rational design of such detection tools. To elucidate the binding of a cationic polythiophene (CPT) to DNA with atomistic resolution, we performed molecular simulations of their supramolecular assembly. Comparison of replicated simulations show a multiplicity of CPT binding geometries that contribute to the wrapping of CPT around DNA. The different binding geometries are stabilized by both electrostatic interactions between CPT lateral cations and DNA phosphodiesters and van der Waals interactions between the CPT backbone and the DNA grooves. Simulated circular dichroism (CD) spectra show that the induced CD signal stems from a conserved geometrical feature across the replicated simulations, i. e . the presence of segments of syn  configurations between thiophene units along the CPT chain. At the macromolecular scale, we inspected the different shapes related to the CPT binding modes around the DNA through symmetry metrics. Altogether, molecular dynamics (MD) simulations, model Hamiltonian calculations of the CD spectra, and symmetry indices provide insights into the origin of induced chirality from the atomic to the macromolecular scale. Our multidisciplinary approach points out the hierarchical aspect of CPT chiral organization induced by DNA. Abstract : Molecular simulations reveal the binding mode multiplicity of a cationic polythiophene (CPT) to DNA. Beyond such a multiplicity, local geometrical features (syn segments) are preserved among the diverse CPT binding modes. These common geometrical patterns are related to the origin of the CPT chirality, induced by its assembly with DNA.